Erdene. - Huang, Edison. (2012)
Driven by the increasing popularity of the 3D platform, from the advertisements, short movies to full feature animated films, the urge to produce a film-piece, which later called Erdene sparked. There are thousands and thousands of 3D advertisement, short movies and animation full film around us nowadays. However, only a little of thousands lasted in the memory of the audience. Erdene is the project that tries to answer the challenge to give impact to the audiences with the stunning story, ending and the style of the movie. Erdene tries to explore the way to manipulate the audience emotion and to present them with unexpected outcome of the movie unlike the common animation film, which has happy ending in the end.